Accumulation of Kv7.2 channels in putative ectopic transduction zones of mice nerve-end neuromas - Lopez-García Jose A; Castillejo Sol; Roza Carolina (SAGE Publishing, 2011)
Abstract Background Modulation of M-type currents has been proposed as a new strategy for the treatment of neuropathic pain due to their role in regulating neuronal excitability. Using electrophysiological techniques we showed previously that the opening of Kv7 channels with retigabine, blocked ectopic discharges from axotomized fibers but did not alter transduction at intact skin afferents. We hypothesized that after nerve damage, accumulation of Kv7 channels in afferent fibers may increase M-type currents which then acquired a more important role at regulating fiber excitability. Findings In this study, we used an immunohistochemical approach to examine patterns of expression of Kv7.2 channels in afferent fibers after axotomy and compared them to patterns of expression of voltage gated Na+ channels (Nav) which are key electrogenic elements in peripheral axons known to accumulate in experimental and human neuromas. Axotomy induced an enlargement and narrowing of the nodes of Ranvier at the proximal end of the neuroma together with a dramatic demyelination and loss of structure at its distal end in which naked accumulations of Nav were present. In addition, axotomy also induced accumulations of Kv7.2 that co-localized with those of Nav channels. Conclusions Whilst Nav channels are mandatory for initiation of action potentials, (i.e. responsible for the generation/propagation of ectopic discharges) an increased accumulation of Kv7.2 channels after axotomy may represent a homeostatic compensation to over excitability in axotomized fibers, opening a window for a peripheral action of M-current modulators under conditions of neuropathy.